A mutation in mouse pak1ip1 causes orofacial clefting while human PAK1IP1 maps to 6p24 translocation breaking points associated with orofacial clefting - Ross, Adam P.; Mansilla, M. Adela; Choe, Youngshik; Helminski, Simon; Sturm, Richard; Maute, Roy L.; May, Scott R.; Hozyasz, Kamil K.; Wójcicki, Piotr; Mostowska, Adrianna; Davidson, Beth; Adamopoulos, Iannis E.; et al. (PLOS ONE, 2013)
Orofacial clefts are among the most common birth defects and result in an improper formation of the mouth or the roof of the mouth. Monosomy of the distal aspect of human chromosome 6p has been recognized as causative in congenital malformations affecting the brain and cranial skeleton including orofacial clefts. Among the genes located in this region is PAK1IP1, which encodes a nucleolar factor involved in ribosomal stress response. Here, we report the identification of a novel mouse line that carries a point mutation in the Pak1ip1 gene. Homozygous mutants show severe developmental defects of the brain and craniofacial skeleton, including a median orofacial cleft. We recovered this line of mice in a forward genetic screen and named the allele manta-ray (mray). Our findings prompted us to examine human cases of orofacial clefting for mutations in the PAK1IP1 gene or association with the locus. No deleterious variants in the PAK1IP1 gene coding region were recognized, however, we identified a borderline association effect for SNP rs494723 suggesting a possible role for the PAK1IP1 gene in human orofacial clefting.
Gesehen am 20.01.2022